2022
DOI: 10.1002/ccr3.6277
|View full text |Cite
|
Sign up to set email alerts
|

Correction of anterior open bite of varying severity using clear aligner therapy—A case series

Abstract: In open bite cases, a comprehensive diagnostic differentiation is crucial in determining the best corrective therapy. In non-surgical open bite treatment, fixed appliances, either labial or lingual, are usually employed. With the addition of extra-radicular screws, more sophisticated orthodontic movements may now be performed without the necessity for orthognathic surgery. Clear aligner therapy, on the contrary, has grown in popularity as a treatment option for more complex cases, such as open bite malocclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In this case a major profile change could be achieved for the patient with improved aesthetics because of the correction of the severe open bite. A combination of miniscrews and MEAW wire was used to re‐orient the occlusal plane, which could substantially change the patient's profile 11–14 . Many contemporary techniques can help orthodontic practitioners achieve a much‐improved patient treatment outcome 15,16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case a major profile change could be achieved for the patient with improved aesthetics because of the correction of the severe open bite. A combination of miniscrews and MEAW wire was used to re‐orient the occlusal plane, which could substantially change the patient's profile 11–14 . Many contemporary techniques can help orthodontic practitioners achieve a much‐improved patient treatment outcome 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…The MEAW technique is complemented with the use of inter-maxillary elastics, occlusal plane, which substantially change the patient's profile. [11][12][13][14] Many contemporary techniques can help orthodontic practitioners achieve a much-improved patient treatment outcome. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…Sabouni et al studied the implication of clear aligners in the treatment of open bite, incorporating three cases: clear aligners alone, clear aligners with attachments and vertical elastics, and clear aligners with attachments and temporary anchorage devices [17]. The research showed satisfactory success in all three scenarios, with auxiliaries treating more complex cases.…”
Section: Open Bite Correctionmentioning
confidence: 99%
“…It emphasized that these types of malocclusions responded better to treatment with clear aligners than fixed appliance therapy because they apply less extrusive force on posterior teeth, which are meant to be intruded in the treatment of open bite. The treatment of open bite with clear aligners involves the combined intrusion of maxillary and mandibular teeth and the combined extrusion of maxillary and mandibular anterior teeth [17].…”
Section: Open Bite Correctionmentioning
confidence: 99%